Manguel, A. (2015). Okumanın tarihi. (F. Elioğlu, Çev.). 7. bs. İstanbul: Yapı Kredi Yayınları. 419 s. 21 cm. Kaynakça ve dizin var. ISBN: 9789753639194 - (:unkn) unknown (My University, 2015)
0
Keywords: Bilgi, Belge Yönetimi